Increasing Entrepreneurship Ability of Student of Sport Science Faculty - Nurul Ihsan; Sepriadi Sepriadi; Suwirman Suwirman (Jurnal Humanities Pengabdian Kepada Masyarakat, 2020)
The main problem in this activity is that the students' abilities are not maximal in relation to entrepreneurship. The main problem lies in the managerial ability of business, administration, product quality and other matters related to entrepreneurship. This is because students involved in this program do not have in-depth understanding and knowledge related to business management. In addition, the process carried out when obtaining funding was not too developed due to the relatively insufficient funding aspect. To overcome this problem, programs are compiled which will be implemented in 3 patterns, namely training, mentoring and mentoring. The type of training that will be provided is hard skills and soft skills training related to entrepreneurship development. The targets of this activity are students who receive grants from the Entrepreneurship Scheme Student Creativity Program and the Student Entrepreneurship Program. Besides that, there are also students who are interested in developing entrepreneurship. This activity was carried out at the Faculty of Sport Sciences, State University of Padang. Implemented from August to October 2020. In accordance with the objectives of this Community Service, the approach pattern to be carried out uses the Participation Actions Learnig System (PALS) pattern. This pattern is a pattern where tenants participate directly in every program that will be provided. The results obtained from the activity: 1) Increase the ability of participants related to entrepreneurial soft skills, 2) Increase the ability of participants related to entrepreneurial hard skills.